Power quality improvement using PV fed series active power filter with enhanced Jaya optimized PI controller - Mallajoshula, Ravikanth; Naidu, I. E. S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
In this paper, improvement of power quality (PQ) in a distribution system using a PV-series active power filter (PV-SAPF) investigated. The performance of the proposed filter is increased using an enhanced Jaya optimized proportional integral (PI) with indirect current controller (ICC) technique system. In existing Jaya optimization technique best and worst cases were obtained from the whole solutions which degrades the output of the PI controller results more iteration. In case of enhanced Jaya, the proposed one, population from best to worst is shorted first and divide them as two groups best and worst solutions. The best solution is chosen from the best solution group as “Best,” and the best solution from the worst solution group is chosen as “Worst”. This procedure decreases the number of iterations needed to reach the optimal solution. The effectiveness of the enhanced Jaya optimization and ICC developed controller is implemented in the proposed PV-SAPF. To proof its effectiveness different types of loads are taken as case study. MATLAB/Simulink platform is used to do the above research work.